Open research, open data, and your development organization: best practices in information and data management for development - Zandstra, Megan; Azubuike, Abraham; Clobridge, Abby; Kuchma, Iryna; Mwanzia, Leroy; Prasai, Nilam; Staiger-Rivas, Simone; Willmers, Michelle; Senmartin, Denise (2017)
Data and information management are key components of enabling a knowledge-sharing environment in the development sector. Improved physical and virtual availability, accessibility, and applicability of data and information increases the chances of it reaching intended audiences and providing them with new insights, evidence, or confirmation of assumptions. In this issue of the KM4Dev Journal, "Open research, open data, and your development organization: Best practices in information and data management for development", we present six cases of open access and open data management approaches in diverse institutional settings around the world.